GERAKAN INVESTASI SYARIAH DALAM PERENCANAAN KEUANGAN BAGI MASYARAKAT DESA KARANG INDAH - Rizqiyah, Talida Silmi; Isfandayani, Isfandayani; Fahlevi, Rizal; Widyananto, Arief; Isnandar, Fajri Ryan (LPPM Universitas Islam 45, 2024)
This community service aims to increase the understanding and participation of the people of Karang Indah Village, Bojongmangu District, Bekasi Regency in making sharia investments to improve the economic welfare of the village community. The problem encountered is that there are still many people in Karang Indah Village who do not understand how to manage finances properly, this causes many people to be trapped in a circle of poverty and difficulties in achieving economic welfare. To overcome this, the service team carried out a community service movement by holding a sharia investment socialization program to increase financial literacy in the community and provide education on how to manage finances effectively and efficiently. The service method uses socialization and assistance to the community in using the Bibit application to make it easier for people to invest. The results of the community service activities showed that this program was successful as seen from the enthusiasm of the community service participants who managed to understand and increase literacy on how to manage finances in investing through the Bibit application